Shareholder Activism by Institutional Investors: Evidence for Calpers. - Smith, Michael P (Journal of Finance, 1996)
This study examines firm characteristics that lead to shareholder activism and analyzes the effects of activism on target firm governance structure, shareholder wealth, and operating performance for the fifty-one firms targeted by the California Public Employees' Retirement System (CalPERS) over the 1987-93 period. Firm size and level of institutional holdings are found to be positively related to the probability of being targeted, and 72 percent of firms targeted after 1988 adopt proposed changes or make changes resulting in a settlement with CalPERS. Shareholder wealth increases for firms that adopt or settle and decreases for firms that resist. No statistically significant change in operating performance is found.